Quantum Spin-Wave Materials, Interface Effects and Functional Devices for Information Applications - Xu, Jiapeng; Jin, Lichuan; Liao, Zhimin; Wang, Qi; Tang, Xiaoli; Zhong, Zhiyong; Zhang, Huaiwu (Frontiers in Materials, 2020)
With the continuous miniaturization of electronic devices and the increasing speed of their operation, solving a series of technical issues caused by high power consumption has reached an unprecedented level of difficulty. Fortunately, magnons (the quanta of spin waves), which are the collective precession of spins in quantum magnetic materials, making it possible to replace the role of electrons in modern information applications. In the process of information transmission, nano-sized spin-wave devices do not transport any physical particles; therefore, the corresponding power consumption is extremely low. This review focuses on the emerging developments of the spin-wave materials, tunable effects, and functional devices applications. In the materials front, we summarize the magnetic properties and preparation characteristics of typical insulating single-crystalline garnet films or metallic alloy films, the development of new spin-wave material system is also introduced. Afterward, we introduce the emerging electric control of spin-wave effects originating from the interface transitions, physical or chemical, among these films including, voltage-controlled magnetic anisotropy, magneto-ionic transport, electric spin-torque, and magnon-torque. In the functional devices front, we summarize and elaborate on the low dispassion information processing devices and sensors that are realized based on spin waves.